2021
DOI: 10.1111/cogs.12945
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Acquisition of Verb Inflection in Typically Developing Children and Children With Developmental Language Disorder in English and Spanish

Abstract: Children with developmental language disorder (DLD) have significant deficits in language ability that cannot be attributed to neurological damage, hearing impairment, or intellectual disability. The symptoms displayed by children with DLD differ across languages. In English, DLD is often marked by severe difficulties acquiring verb inflection. Such difficulties are less apparent in languages with rich verb morphology like Spanish and Italian. Here we show how these differential profiles can be understood in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…So, for example, Bortolini et al (1998) have shown that when tested on their use of grammatical morphology, Italian-acquiring children with SLI (age 4;2-6;3) performed significantly better than their English-acquiring counterparts. Similar findings have been reported for a number of other morphological rich languages, such as Hungarian (Lukács et al, 2009), Kannada (Tiwari et al, 2017), and Spanish (Bedore & Leonard, 2005;Freudenthal et al, 2021). Despite the wealth and breadth of research on finiteness marking in SLI crosslinguistically, and although considerable attention has been paid to the investigation of verbal inflectional morphology in TD Russian, to the best of our knowledge, there exists no study directly investigating finiteness marking in monolingual Russian SLI.…”
Section: Finiteness Marking In Slisupporting
confidence: 80%
See 2 more Smart Citations
“…So, for example, Bortolini et al (1998) have shown that when tested on their use of grammatical morphology, Italian-acquiring children with SLI (age 4;2-6;3) performed significantly better than their English-acquiring counterparts. Similar findings have been reported for a number of other morphological rich languages, such as Hungarian (Lukács et al, 2009), Kannada (Tiwari et al, 2017), and Spanish (Bedore & Leonard, 2005;Freudenthal et al, 2021). Despite the wealth and breadth of research on finiteness marking in SLI crosslinguistically, and although considerable attention has been paid to the investigation of verbal inflectional morphology in TD Russian, to the best of our knowledge, there exists no study directly investigating finiteness marking in monolingual Russian SLI.…”
Section: Finiteness Marking In Slisupporting
confidence: 80%
“…To take it a step further, such a correlation suggests that it may be interesting to explore the Russian SLI data in light of various input-driven accounts of OI errors (see e.g. Freudenthal et al, 2021;Pine et al, 2020, and references therein). We leave such an investigation for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bybee and Brewer ( 1980 ) have further pointed out that semantic overlap also matters in the expected way: the more similar two forms are in meaning, the more likely they are to influence each other in paradigm leveling. Hoeffner and McClelland ( 1993 ) have shown that parallel activation of morphologically-related forms from shared semantics can also explain the paradigm leveling that occurs in child language acquisition, where children (particularly, those with developmental language delay, previously called specific language impairment) substitute frequent base forms for less frequent inflected forms (see also Freudenthal et al, 2021 ; Harmon et al, 2021 ).…”
Section: Planning: a Flexible Interactive Processmentioning
confidence: 99%
“…The other grammatical property of a verb proposed by Freudenthal, Ramscar, Leonard, and Pine (2021) is that it inflects for tense morphologically. Besides its base form, a verb has at most four inflected forms, formed by adding one of the suffixes to the base form, i.e., +n for the past participle, +d for past tense or past participle, +s for the third person singular present tense, and +ing for progressive.…”
Section: Conditions For Try and V Constructionmentioning
confidence: 99%